2021
DOI: 10.1088/1755-1315/905/1/012092
|View full text |Cite
|
Sign up to set email alerts
|

Pasting properties of jack bean (Canavalia ensiformis) modified starch with heat moisture treatment

Abstract: Jack bean is a local legume that can grow in suboptimal land and potential to be developed in Indonesia. Jack bean seed has 33.32% of protein and 61.15% of carbohydrate so it can become a starch source for the food industry. Native starch has a limited application on food products because of its weak characteristics such as being unstable to heat and shear. Heat Moisture Treatment (HMT) starch modification is needed to overcome the weaknesses. HMT is a natural modification because it does not leave a chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The results showed that HMT could improve the gelatinization properties of chickpea starch. HMT increased the short-range ordered structure of starch granules, decreased the swelling power of starch granules, decreased the viscosity of starch granules, and increased the gelatinization temperature of starch granules (Ariyantoro et al, 2021). The water-binding capacity and thickening ability of starch granules were characterized by peak viscosity.…”
Section: Changes Of Viscosity Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…The results showed that HMT could improve the gelatinization properties of chickpea starch. HMT increased the short-range ordered structure of starch granules, decreased the swelling power of starch granules, decreased the viscosity of starch granules, and increased the gelatinization temperature of starch granules (Ariyantoro et al, 2021). The water-binding capacity and thickening ability of starch granules were characterized by peak viscosity.…”
Section: Changes Of Viscosity Propertiesmentioning
confidence: 97%
“…In addition, starch can also be used as food packaging raw materials (Costa et al, 2021). However, in most cases, the properties of natural starch are not ideal, because of high viscosity, low solubility, thermal decomposition and poor stability, and other factors, its use is limited (Ariyantoro et al, 2021). For example, in long-term heating, acidic environment or high shear, gelatinization stability is poor, leading to the breakdown of the starch gel network (Acevedo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Jack beans have an average productivity of 7 tons/hectare, with a potential yield of 12 tons/hectare. Moreover, the average yearly production (Indonesia) of 5 tons of jack beans comes from 1,590 hectares of land (Ariyantoro et al, 2021). It is widely accessible throughout Latin America, Africa, Asia, the West Indies, Indonesia, and India (Marimuthu and Gurumoorthi, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for a long time, countries all over the world have attached great importance to the development and utilization of starch resources [ 5 ]. But the nature of native starch (NS) is not ideal, usually there is thermal decomposition, low solubility, and other defects [ 6 ]. For example, the gelatinization stability of native starch is poor, easy to dehydrate in the freezing process, and the freeze–thaw stability is not good [ 7 ].…”
Section: Introductionmentioning
confidence: 99%